1985
DOI: 10.2307/3899332
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed Burning in the Loess Hills Mixed Prairie of Southern Nebraska

Abstract: Abused rangelands dominated by introduced cool-season gmsses and warm-season shortgrasses are common over much of the Mixed Prairie. Native decreaser species are primarily warm-season grasses and are present at only hwigniflcant levels on abused rangeland in the Loess Hills of southcentral Nebraska. A single, Iatespring, prescribed fire was evaluated as II method of improvement. The study area consisted of 3 tracts of plots located on Holdrege silt loam soil (Typic Argiustall) with an average annual precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
5
16
1
Order By: Relevance
“…Similar negative fire responses in black grama have been noted throughout its range (Reynolds and Bohning 1956;Jameson 1962;Cable 1965;Wright 1980;Drewa and Havstad 2001;Peters and Gibbens 2006). The other grass species examined in this study (purple three-awn and spike dropseed) also showed negative fire impacts and multiyear recovery times, a finding that is generally consistent with previous studies on Aristida (Christensen 1964;Trlica and Schuster 1969;Wright 1974;Steuter and Wright 1983) and Sporobolus species (Hopkins et al 1948;Christensen 1964;Stinson and Wright 1969;Wright 1980;Rasmussen et al 1986;Higgins et al 1989; but see Schacht and Stubbendieck 1985 for positive fire effects on Sporobolus).…”
Section: Discussionsupporting
confidence: 91%
“…Similar negative fire responses in black grama have been noted throughout its range (Reynolds and Bohning 1956;Jameson 1962;Cable 1965;Wright 1980;Drewa and Havstad 2001;Peters and Gibbens 2006). The other grass species examined in this study (purple three-awn and spike dropseed) also showed negative fire impacts and multiyear recovery times, a finding that is generally consistent with previous studies on Aristida (Christensen 1964;Trlica and Schuster 1969;Wright 1974;Steuter and Wright 1983) and Sporobolus species (Hopkins et al 1948;Christensen 1964;Stinson and Wright 1969;Wright 1980;Rasmussen et al 1986;Higgins et al 1989; but see Schacht and Stubbendieck 1985 for positive fire effects on Sporobolus).…”
Section: Discussionsupporting
confidence: 91%
“…However, the influence of initial grassland species composition is clearly shown in a study by Schacht and Stubbendieck (1985) in the loess hills of Nebraska. These investigators found that reduced cool season herbage yield (mainly Poa pratensis) persisted for two years in tracts where warm season grasses were initially present, but was short-lived on a tract where the warm season component was missing.…”
Section: Management/monitoring Management Requirementsmentioning
confidence: 99%
“…Four studies, including Anderson et al (1970), Heirman and Wright (1973), Schacht and Stubbendieck (1985), and White and Currie (1983), reported results from spring fires ranging from negative or neutral, to positive responses, over a time frame of 3 months to 16 years (Ford, 1999). Separation of spring burns into early-and latespring categories revealed that early spring (March) burns produced neutral or positive responses, and late-spring burning (May) produced negative results (Anderson et al, 1970;Heirman and Wright, 1973;Ford, 1999).…”
Section: Perennial Grass Covermentioning
confidence: 99%
“…Over time, fall burns produced more herbage than did spring burns (White and Currie, 1983). However, a late-spring (April) burn by Schacht and Stubbendieck (1985) showed a positive response by blue grama and a neutral response by buffalograss (Ford, 1999).…”
Section: Perennial Grass Covermentioning
confidence: 99%